3D-conformal radiotherapy for inoperable non-small-cell lung cancer - Fromm, Sabine (Radiology and oncology (Ljubljana), 2007)
Background. The purpose of this investigation was to evaluate feasibility, safety and efficacy of 3D conformal radiotherapy (3D-RT) for inoperable non-small-cell lung cancer (NSCLC). Time to progression (TTP), including localrecurrence and/or distant metastasis, local control rate (LCR), time to death (TTD) and side effects were evaluated. Patients and methods. From 1997 to 2002, a total of 84 patients with inoperable NSCLC were treated with 3D-RT according to a prospective protocol at our institution. Depending on performance status, lung function and dose-volume constraints, radiation dosesof either 66-70 Gy or 50-60 Gy +/- platin-based chemotherap were applied.Results. The treatment was well tolerated and the rate of side effectswas low. Only one grade 4 pneumonitis was observed, the rate of grade 3pneumonitis was 6% and 13% for grade 2. Two patients developed a grade 4 oesophagitis and no grade 3 oesophageal toxicity was observed. The analysis ofdose-volume histograms (DVH) found a mean V20 (lung volume that receives 20 Gy) for the ipsilateral lung (IL) of 42%, a mean V20 for the contralateral lung (CL) of 14% and a mean lung dose IL of 25 Gy. The mean V20 IL in patientsdeveloping a pneumonitis grade 2-4 was 53.3%. The mean follow-up was 24 month. There was no difference in TTP (median 15 months) in the different treatment groups. Patients receiving higher radiation doses (66-70 Gy) had a benefit in an overall survival (OS) when the additional chemotherapy was applied (28 month vs. 16 month). Local control rates of mean 22% after 2 yearswere low. Conclusions. The application of radiation doses up to 70 Gy is feasible and safe, also in combination with chemotherapy. Still, the local control and OS is poor. Thus, further trials to investigate the possibility ofdose escalation in the lung without increasing lung toxicity significantly, also in more advanced tumour stages, are mandatory.
Keywords: Carcinoma, Non-Small-Cell Lung; Dose-Response Relationship, Radiation; Doza-odgovor, odnos, sevanje; Karcinom nemalocelični, pljučni; Lung Neoplasms; pljuča; Pljučne novotvorbe; pljučni rak; Preživetje, analiza; radiologija; radioterapija; Radioterapija, planiranje z računalnikom; Radiotherapy; Radiotherapy Planning, Computer-Assisted; Survival Analysis; zdravljenje